Smarties: User-friendly codes for fast and accurate calculations of light scattering by spheroids. (May 2016) - Somerville, W.R.C.; Auguié, B.; Le Ru, E.C.
Abstract: We provide a detailed user guide forsmarties, a suite ofMatlab codes for the calculation of the optical properties of oblate and prolate spheroidal particles, with comparable capabilities and ease-of-use as Mie theory for spheres.smarties is aMatlab implementation of an improved T -matrix algorithm for the theoretical modelling of electromagnetic scattering by particles of spheroidal shape. The theory behind the improvements in numerical accuracy and convergence is briefly summarized, with reference to the original publications. Instructions of use, and a detailed description of the code structure, its range of applicability, as well as guidelines for further developments by advanced users are discussed in separate sections of this user guide. The code may be useful to researchers seeking a fast, accurate and reliable tool to simulate the near-field and far-field optical properties of elongated particles, but will also appeal to other developers of light-scattering software seeking a reliable benchmark for non-spherical particles with a challenging aspect ratio and/or refractive index contrast. Abstract : Highlights: A free and user-friendly program to simulate electromagnetic scattering by spheroids. Detailed description of the program including input parameters and range of validity. Examples of use relevant to plasmonics, with far-field and near-field calculations. Summary of the underlying theoretical framework, including our recent improvements.